2010
DOI: 10.1186/1471-2458-10-769
|View full text |Cite
|
Sign up to set email alerts
|

Mistrust in marriage-Reasons why men do not accept couple HIV testing during antenatal care- a qualitative study in eastern Uganda

Abstract: BackgroundA policy for couple HIV counseling and testing was introduced in 2006 in Uganda, urging pregnant women and their spouses to be HIV tested together during antenatal care (ANC). The policy aims to identify HIV-infected pregnant women to prevent mother-to-child transmission of HIV through prophylactic antiretroviral treatment, to provide counseling, and to link HIV-infected persons to care. However, the uptake of couple testing remains low. This study explores men's views on, and experiences of couple H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
105
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(127 citation statements)
references
References 28 publications
(25 reference statements)
21
105
1
Order By: Relevance
“…The high reported levels of HIVrelated communication are encouraging and suggest the normalisation of HIV (Zuch & Lurie, 2012). Consistent with previous published research, we observed higher levels of MPI among participants who reported higher levels of communication with partners (Ditekemena et al, 2012;Kalembo et al, 2012;Reece et al, 2010) and stable relationship status (Ditekemena et al, 2012;Larsson et al, 2010;Morfaw et al, 2013). The high reported levels of MPI overall indicate that gender norms may be shifting, with men becoming more involved in pregnancy.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The high reported levels of HIVrelated communication are encouraging and suggest the normalisation of HIV (Zuch & Lurie, 2012). Consistent with previous published research, we observed higher levels of MPI among participants who reported higher levels of communication with partners (Ditekemena et al, 2012;Kalembo et al, 2012;Reece et al, 2010) and stable relationship status (Ditekemena et al, 2012;Larsson et al, 2010;Morfaw et al, 2013). The high reported levels of MPI overall indicate that gender norms may be shifting, with men becoming more involved in pregnancy.…”
Section: Discussionsupporting
confidence: 92%
“…Discussion around antenatal care and pregnancyrelated financial support, however, was reported as the most prevalent form of involvement, as observed in other contexts (Byamugisha et al, 2010;Nkuoh et al, 2010). Being able to attend antenatal visits depends on a variety of factors (Montgomery et al, 2011), and our research found that men who were forced to wait outside questioned the necessity of accompanying their partners to the clinic, as reported elsewhere (Larsson et al, 2010). Given these constraints, interventions to increase MPI in pregnancy more generally may be more beneficial than attempting to increase rates of male attendance at antenatal visits (Jones et al, 2013).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…In the Tanzanian randomized VCT study, there were significant differences between women assigned to couple VCT who completed it and those who did not, and the authors attributed the higher rates of risk reduction in the couple VCT arm to its selectivity of committed individuals (Becker et al, 2010). Likewise, in a qualitative study, Ugandan men believed that couple VCT participants had solid, caring relationships (Larsson et al, 2010), which is likely the type of relationship needed to implement risk reduction strategies. Couple counseling is also selective in that both partners have to be available at the same time to use the service.…”
Section: Introductionmentioning
confidence: 94%
“…Couple counseling is also selective in that both partners have to be available at the same time to use the service. Job responsibilities or time constraints can make this difficult for some couples (Kebaabetswe et al, 2010;Larsson et al, 2010;Mlay, Lugina, & Becker, 2008).…”
Section: Introductionmentioning
confidence: 99%